An ethical analysis of HIV self-testing in South Africa using principlist, and human rights approaches, including a benefit/harm analysis - Hermanus, Tandile (My University, 2019)
This research report explores the ethical implications of using the HIV self-testing kit as an innovative testing tool to expand access to HIV testing services and potentially increase HIV testing uptake in South Africa among individuals who may otherwise not test, as they may want to test for HIV in private or at their own convenience. The arguments are drawn from the principle of autonomy, principles of beneficence and non-maleficence, as well as the principle of justice. In addition, the ethical theory of utilitarianism is used in a harm/benefit analysis to further support my arguments. The research method employed is purely normative and derives information from the available literature on HIV self-testing. The conclusion reached in this research report is that the implementation and scale-up of HIV self-testing in South Africa is ethical, as self-testing does not violate any of the ethical principles and has the potential to provide more benefits than harms. However, the potential for coercion and intimate partner violence surrounding HIV self-testing remain issues of concern, as these occurrences would challenge the principle of non-maleficence in the use of the kit. However, empirical data on the potential social harms do not provide compelling ethical grounds for restricting the sale of HIVST kits in South Africa.
research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Masters of Science in Medicine in Bioethics and Health Law. Johannesburg,2019